Effect of energy losses at processing phase manipulated signals to a maximum range and accuracy processing coordinate in landing radar - G. S. Nakhmanson; A. V. Suslin (Известия высших учебных заведений России: Радиоэлектроника, 2015)
Deterioration maximum range and accuracy of measurement range and angular coordinates caused by energy losses during processing phase manipulated radio signals is considered. It has been shown that a decrease of energy losses is possible by using a phase-manipulated signals with smoothly changing phase between the elementary pulses.